2020
DOI: 10.3390/md18090433
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Using Ecklonia stolonifera Protect Human Dermal Fibroblasts from UVA-Induced Senescence through Inhibiting MMP-1 and MMP-3

Abstract: The effect of gold nanoparticles (GNPs) synthesized in marine algae has been described in the context of skin, where they have shown potential benefit. Ecklonia stolonifera (ES) is a brown algae that belongs to the Laminariaceae family, and is widely used as a component of food and medicine due to its biological activities. However, the role of GNPs underlying cellular senescence in the protection of Ecklonia stolonifera gold nanoparticles (ES-GNPs) against UVA irradiation is less well known. Here, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…AuNSs were synthesized by optimizing the concentration, temperature, and reaction time of the PT extract and metal precursor. First, aqueous HAuCl 4 ·3H 2 O solution (1M) was added to the PT extract (4 mg·mL −1 ), and the mixture was incubated in a water bath at 80 °C for 15 min [ 47 ]. The tube containing PT-AuNSs was placed on ice for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…AuNSs were synthesized by optimizing the concentration, temperature, and reaction time of the PT extract and metal precursor. First, aqueous HAuCl 4 ·3H 2 O solution (1M) was added to the PT extract (4 mg·mL −1 ), and the mixture was incubated in a water bath at 80 °C for 15 min [ 47 ]. The tube containing PT-AuNSs was placed on ice for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The morphology and particle size distribution of PT-AuNS were determined using HR-TEM TALOS F200X (Thermo Scientific, Waltham, MA, USA) at an electron potential of 200 kV. To confirm that PT-AuNS were synthesized via PT extraction, FTIR spectra were obtained using the Spectrum GX spectrometer (Perkin Elmer Inc., Boston, MA, USA) prepared with potassium bromide pellets [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antisenescence effect of ES-GNPs in a human dermal fibroblasts (HDF) senescence model induced by ultraviolet A (UVA) irradiation was investigated. The results showed that ES-GNPs exerted antisenescence effects on UVA-irradiated HDF by inhibiting MMP-1/-3 expression and SA-β-galactosidase activity [ 75 ]. In addition, fucosterol extracted from ES down-regulated the expression of glucose-regulated protein 78 to alleviate soluble amyloid beta peptide 1–42 -induced cognitive impairment in aging rats [ 33 ].…”
Section: Bioactivitiesmentioning
confidence: 99%